2016
DOI: 10.5665/sleep.6328
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and Behavior in Cross-Fostering Rats: Developmental and Sex Aspects

Abstract: Study Objective: Adverse early-life events induce behavioral psychopathologies and sleep changes in adulthood. In order to understand the molecular level mechanisms by which the maltreatment modifies sleep, valid animal models are needed. Changing pups between mothers at early age (cross-fostering) may satisfyingly model adverse events in human childhood. Methods: Cross-fostering (CF) was used to model mild early-life stress in male and female Wistar rats. Behavior and BDNF gene expression in the basal forebra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…In fact, both animal and human studies have found prenatal maternal anxiety and depression to be associated with sleep difficulties at early ages. For instance, experimental animal research shows that prenatal and early postnatal stress are associated with long‐lasting structural sleep changes in the offspring mimicking those reported in depression (Santangeli et al., ). The underlying mechanism of such long‐term effects of prenatal conditions is believed to be the inhibition of the 11ß‐hydroxysteroid dehydrogenase type 2 (HSD2) placental enzyme, which is responsible for inactivation of excessive maternal glucocorticoids (Harris & Seckl, ).…”
Section: Discussionmentioning
confidence: 90%
“…In fact, both animal and human studies have found prenatal maternal anxiety and depression to be associated with sleep difficulties at early ages. For instance, experimental animal research shows that prenatal and early postnatal stress are associated with long‐lasting structural sleep changes in the offspring mimicking those reported in depression (Santangeli et al., ). The underlying mechanism of such long‐term effects of prenatal conditions is believed to be the inhibition of the 11ß‐hydroxysteroid dehydrogenase type 2 (HSD2) placental enzyme, which is responsible for inactivation of excessive maternal glucocorticoids (Harris & Seckl, ).…”
Section: Discussionmentioning
confidence: 90%
“…The day when pregnancy was confirmed by vaginal smear (Cannizzaro et al, 2008 ; Plescia et al, 2014b ), designed as gestational day 1 (GD1), eight female rats were randomly selected from each experimental group ( n = 12), housed in standard maternity cages, filled with wood shavings. Dams were inspected twice daily for delivery until the day of parturition, considered as postnatal day 0 (PND 0); dams and litters were kept in a nursery (24 ± 2°C) and not separated until weaning, in order to model the human condition and avoid confounding factors (Subramanian, 1992 ; Wilson et al, 1996 ; Santangeli et al, 2016 ). Mean alcohol consumption at 1 h and 24 h by CAD and IAD rat dams during pre-conception period, gestation, and lactation was recorded and reported as g/kg ± SEM.…”
Section: Methodsmentioning
confidence: 99%
“…Female rats underwent the self-administration procedure throughout pregnancy, accordingly to the respective two-bottle choice paradigm. Dams were inspected twice daily for delivery until the day of parturition, considered as postnatal day 0 (PND 0); dams and litters were kept in a nursery (24 ± 2°C) and not separated until weaning, in order to avoid confounding effects due to cross-fostering procedure [ 43 45 ] and model the human condition.…”
Section: Methodsmentioning
confidence: 99%